Tablas de datos Chemical composition, physicochemical properties and antioxidant potential of Argentine Brown Teff - Ripari Garrido, Juliana (2026)
Composition of Argentinean teff flour compared with values reported by other authors. Values are expressed as g per 100 g of teff flour. Minerals of Argentinean teff flour compared with values reported by other authors. Values expressed as mg of mineral per 100 g of flour. Fatty acids profile of Argentinean teff flour compared with values reported by other authors. Values are expressed as g of fatty acids per 100 g of lipids. Total amino acids profile of Argentinean teff flour compared with values reported by other authors. Values expressed as g of amino acid per 100 g of protein.